WHAT CHARACTERISES CHAMPION RUNNERS' MANAGEMENT OF INJURY AND ILLNESS? QUALITATIVE STUDY AT IAAF ATHLETICS WORLD CHAMPIONSHIPS. Issue 4 (1st February 2017) - Timpka, Toomas; Bargoria, Victor; Halje, Karin; Jacobsson, Jenny
Abstract : Background: International sports bodies are increasingly on the lookout to balance the excitement of elite sport with the risk that is inevitable. For further understanding of these risks, athletes' reports on how sensations of pain, discomfort, and loss of functioning are interpreted and acted upon are vital. Objective: To explore what characterizes injury and illness management among champion runners. Design: Qualitative study using in-depth interviews for data collection. Setting: Middle- and long-distance runners at IAAF World Athletics Championships. Participants: 12 international runners competing for championships medals. Assessment of Risk Factors: Thematic analysis to generate understanding reasoning about injury and illness. Main Outcome Measurements: Qualitative model describing champion runners' injury and illness management over time. Results: The athletes' behaviours and decisions-making procedures were summarised in the main themes resilience and exigency. Resilience behaviour was constituted of ordinary rather than extraordinary actions and is characterised by a proneness for learning, dynamic adaptations to unforeseen circumstances, and focusing on long-term objectives. The theme prompting and learning describes intense information-seeking performed when experiencing symptoms of injury or illness in order to understand causes and guide responses. This quest for information and knowledge comprised early consultation with clinicians and execution of diagnostic tests, dialogue with coaches, and discussions with peers. The themes effects and consequences describe the short-term outcomes of the athletes' decision-making and their standpoints on how their injury and illness management impacts their overall career, respectively. Conclusions: A model of injury and illness management among champion runners has been developed. The model offers a positive outlook on progress in sports where overuse injuries are common, and a direction for policies aimed at protection of top-level athletes. Resilience behaviour arises from dynamic adaptations of normal functions, meaning that the greatest threats to health maintenance in this group of athletes are those that compromise such adaptations.